Unusual Branching Pattern of Axillary and Brachial Arteries in the Right Upper Limb – A Case Report - Surekha DS; Nayak SB; Prasad AM; Srinivas RS; Cilwyn SB (Faculty of Medicine, UKM Medical Centre, 2015)
Variations of the vascular pattern of proximal part of the upper arm are very common. Knowledge of anomalies in the origin and course of principal arteries is important for the vascular radiologists and surgeons. Several variations of the axillary artery, brachial artery and theirs branches have been reported. We found a common trunk (about 3cm long) of lateral thoracic and subscapular arteries from the axillary artery and a common trunk (about 4cm long) of posterior circumflex humeral and profunda brachii arteries from brachial artery. The profunda brachii artery ran downwards along with radial nerve and entered the radial groove. The posterior circumflex humeral artery hooked around the aponeurosis of latissimus dorsi muscle and supplied its usual area around the glenohumeral joint.